Determinantes da gestão da cadeia de suprimentos sustentável: uma análise da relação entre as pressões e as práticas socioambientais em indústrias de transformação - Abdala, Etienne Cardoso (2013)
In recent years, sustainable development is considered to be one of the most relevant and critical issues in the organizational field. Its relationship to the configuration of production enterprises has become increasingly closer, especially regarding concerns related to the preservation of the environment, to the prudent use of resources and to social demands. Sustainability has become an inherent element in organizational processes, in particular regarding the environment and the supply chain management. The influence of internal and external stakeholders can be crucial for the adoption of sustainable practices. In order to contextualize the scenario, studies firstly address issues of sustainable development and corporate social responsibility, relating sustainability to the organization of the production system. Then, it presents the evolution of the concept of supply chain management relating it to the building up of sustainable supply chains, keeping in mind the effects that the determinants of sustainability exercise on the practices carried out in the supply chain. Considering the theoretical assumptions presented, this research aims at analyzing the relationship which external pressures and internal factors exercise on the adoption of socioenvironmental practices in the context of sustainable supply chain management. To fulfill this goal, two distinct models of measurement were defined: 1) the pressures that determine the practices 2) the socio-environmental practices carried out by companies. The methodology used was based on a survey performed in some processing industries in the State of Minas Gerais. As a form of data analysis, simple descriptive statistics, exploratory and confirmatory factor analysis were performed in order to validate the two proposed models. Finally, a technique of multiple linear regressions was applied to verify the relationship of association between the pressures and practices established by the revised measurement models. The results indicate that although some sources of external pressures are related to the adoption of certain practices, it is the internal organizational aspects that exercise significant influence on socio-environmental practices.